Análise epidemiológica de acidentes ofídicos no estado do Tocantins no período de 2014 a 2018 - Cavalcante, Álvaro Rossano (Universidade Federal do Tocantins, 2021)
Snakes are distributed globally, adapting to the most diverse environments. Nearly 3,000 species of snakes are of scientific knowledge, 386 of which can be found in Brazil. Snakebites are an important public health problem, and their potential harm is determined by the time interval between the bite until initial care and appropriate treatment. The following study aimed to assess the epidemiological profile of ophidic accidents in the state of Tocantins from 2014 to 2018. A cross-sectional, descriptive and retrospective study was carried out analyzing snakebite data recorded in the Notifiable Diseases Information System (SINAN) during the period of 2014 until 2018 in the state of Tocantins. Research was carried out in accordance to Resolution No. 466/2012 of the National Health Council (CNS). In the period of 2014 to 2018 the state of Tocantins recorded 4088 cases of snakebites, a total of 817.6 new cases per year, reflecting an average annual incidence of 53.37 cases / 100.000 inhabitants. The highest frequencies were observed in men, mixed race, economically active population, and those with low education. There was greater involvement in rural areas, totaling 79.13% of the cases, and a decrease in incidence in the driest and warmest months of the year, mainly August and September. Bothropic accidents were the most frequent, and the most common location of the bite was on feet, with the accumulated incidence of lower limbs exceeding 75% of the cases. Most of the cases were minor accidents, and the time interval between the bite and medical attention was less than 6 hours in 81,9%. The incidence of snakebites in Tocantins in the analyzed period was higher than that of the rest of Brazil, which reinforces the importance of ophidic accidents in the region. The profile of the affected population and the type of accident are in accordance with the national standard. Monthly distribution of snakebite accidents is seasonal, with a reduction in the months of August and September, which can be explained by lower rainfall levels. Healthcare after the injury occurred within 3 hours in more than 50% of cases. However, it is still necessary to decrease time until initial care, and therefore the complications and consequences of such accidents.